KOORDINASI SUPPLY CHAIN SATU PABRIK-SATU DISTRIBUTOR PADA MODEL PENENTUAN HARGA DAN KEPUTUSAN PRODUKSI - Yuliawati, Evi (Department Industrial Engineering, University of Muhammadiyah Malang, 2009)
Competition and global market induce enterprises to meet their customer needs on product/ service in considerably cheap price, in acceptable quality and within short lead time. This leads to the fact that coordination in a supply chain is extremely important. This research compare an one manufacturer-one distributor supply chain coordination scenarios in a model joint pricing and production/order decisions. Model joint pricing and production/order decisions is based on Non Linear Programming with objective function to maximize its supply chain profit.Pricing scheme is initiated when the manufacturer determines its selling price. A supply chain coordination scenario and supply chain without coordination scenario will compare in this research. Experiment by employing a set of numerical example is performed to evaluate the model performance. Moreover, sensitivity analysis is done to explore the effect of capacity?s and price to demand sensitivity-parameter?s changes to the objective function of proposed model.